Pengaruh Kombinasi Latihan Burpee-Shooting Terhadap Hasil Tembakan Free Throw pada Peserta Putra Ekstrakurikuler Basket di SMP Negeri 7 Kota Malang - Dona El Shinta; Supriyadi Supriyadi; Heri Purnama Pribadi (Universitas Palangka Raya, 2023)
The game of basketball is a big ball game played by two teams of five players whose objective is to get as many balls into the opponent's basket as possible. The purpose of this study was to measure the effect of burpee practice on penalty shot or free throw outcomes in men's outdoor basketball participants in the SMP Negeri 7 Malang City. The research methodology used in this study is an experimental study with a one-group pretest-posttest design. The study sample consisted of his 20 male college students who participated in a basketball extracurricular activity. The burpee shooting treatment was performed by him for 4 weeks at a frequency of 4 times a week. Burpee shooting practice increased the free throw shooting score of men's outdoor basketball participants in SMP Negeri 7 Malang City, with a significance level of 0.00<0.05.